2016
DOI: 10.1590/0103-9016-2015-0245
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait locus mapping associated with earliness and fruit weight in tomato

Abstract: The flowering time is regarded as an important factor that affects yield in various crops. In order to understand how the molecular basis controlling main components of earliness in tomato (Solanum lycopersicum L.), and to deduce whether the correlation between fruit weight, days to flowering and seed weight, is caused by pleiotropic effects or genetic linkage, a QTLs analysis was carried out using an F 2 interspecific population derived from the cross of S. lycopersicum and S. pimpinellifolium. The analysis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…Regarding the offspring generated from crosses LOR x Reserva, the plants that displayed early flowering in the first cluster increased their total amounts of fruits, average weight of fruits, and total weight of fruits. These results are similar to the correlations reported by Hernández-Bautista et al (2016), who found a positive effect in early flowering in regard to the average weight of fruits and final yield. Genotypes 2051Genotypes , 2019Genotypes , 2054Genotypes , 2069Genotypes , 2096Genotypes , 2061Genotypes , 2015Genotypes , 2080Genotypes , and 2071 were identified as advanced lines with similar characteristics to the control, out of which the advanced lines with origins LOR85 x C, LOR85 x L, LOR91 x C stood out.…”
Section: Correlationssupporting
confidence: 92%
“…Regarding the offspring generated from crosses LOR x Reserva, the plants that displayed early flowering in the first cluster increased their total amounts of fruits, average weight of fruits, and total weight of fruits. These results are similar to the correlations reported by Hernández-Bautista et al (2016), who found a positive effect in early flowering in regard to the average weight of fruits and final yield. Genotypes 2051Genotypes , 2019Genotypes , 2054Genotypes , 2069Genotypes , 2096Genotypes , 2061Genotypes , 2015Genotypes , 2080Genotypes , and 2071 were identified as advanced lines with similar characteristics to the control, out of which the advanced lines with origins LOR85 x C, LOR85 x L, LOR91 x C stood out.…”
Section: Correlationssupporting
confidence: 92%
“…The prediction values for days to flowering of the first inflorescence ranged from 0.38 to 0.41, whereas the range increased from 0.53 to 0.55 for days to flowering of the third inflorescence. In a previous study, we detected a major QTL at flowering called dfft1.1, which increased its effect over time when measured from the first to third truss (Hernández-Bautista et al, 2016b). Therefore, the increasing range found in the present study could be explained by the increased effect of dfft1.1, showing that this QTL increases the prediction accuracy of the statistical model.…”
Section: Discussionsupporting
confidence: 72%
“…This same pattern was observed by Hernández-Bautista et al (2016a), who reported that the prediction accuracy of GBLUP and LASSO increased when it was evaluated for traits with heritability greater than 0.6. Previous classical and molecular studies classified days to ripening and emergence as traits with an intermediate or low heritability, and that they are controlled by small QTL effects (Grandillo and Tanksley, 1996;Haggard et al, 2015;Hernández-Bautista et al, 2016b). Therefore, the poor predictive ability found in the models for both traits occurred because both traits are controlled by many minor QTLs and the limited number of markers used in the present study.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations